2019
DOI: 10.2147/idr.s236766
|View full text |Cite
|
Sign up to set email alerts
|

<p>Emergence of Almost Identical F36:A-:B32 Plasmids Carrying <em>bla</em><sub>NDM-5</sub> and <em>qepA</em> in <em>Escherichia coli </em>from Both Pakistan and Canada</p>

Abstract: The New Delhi Metallo-β-lactamase (NDM) producing Enterobacteriaceae is spreading worldwide. Although the bla NDM gene has been identified in animal associated Enterobacteriaceae isolates in many countries, little is known about its occurrence in animal products in Pakistan. In this study, 13 Escherichia coli isolates were collected from chicken meat samples in Pakistan. Two isolates, 15978 and C4109, exhibited reduced susceptibility (MIC ≥1 μg/mL) to imipenem, and carried bla NDM-5 and bla NDM-7 gene, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…Nevertheless, their carriage rate of bla NDM is higher among the other carbapenem-resistant genes [ 35 ]. The finding of NDM-bearing IncX3 in K. pneumoniae in the present study and E. coli in other studies from Pakistan suggests the distinctive role of IncX3 plasmids in intergeneric bla NDM-1 transmission [ 32 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Nevertheless, their carriage rate of bla NDM is higher among the other carbapenem-resistant genes [ 35 ]. The finding of NDM-bearing IncX3 in K. pneumoniae in the present study and E. coli in other studies from Pakistan suggests the distinctive role of IncX3 plasmids in intergeneric bla NDM-1 transmission [ 32 ].…”
Section: Discussionsupporting
confidence: 75%
“…To the best of our knowledge, this is the first study from CP-KP clinical isolates in Pakistan that has bla NDM-1 -bearing IncX3 plasmids. Only one study from Pakistan demonstrated the MBL gene, i.e., NDM-7 occurrence on IncX3 plasmids in E. coli isolated from Chicken meat samples [ 32 ]. However, IncX3 bearing NDM genes are prevalent in other regions of the world, have a limited host range, and are mainly observed in Enterobacteriaceae [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ST156 and ST405 having bla NDM-1 are previously detected from chicken meat and clinical isolates. 33 , 48 ST156 and ST405 bearing mcr-1 have been detected in other countries like ST156 in Brazil and China and ST405 in Algeria and United States. 49–52 ST156 and ST405 belong to avian-pathogenic E. coli lineage and extra-intestinal pathogenic E. coil .…”
Section: Discussionmentioning
confidence: 94%
“…Other transposable elements have been identified in GNB in Africa; in Nigeria, Tn 5403 truncated IS 3000 in K. quasipneumoniae isolates; 130 interestingly, this genetic structure was also detected in bla NDM‐7 –positive E. coli isolated from a food sample in Pakistan 188 . Also, in South Africa four transposable elements were detected, namely, TniB NTP–binding protein; TniA putative transposase, resolvase, or integrase; TinR protein; and TniQ in K. pneumoniae 79 .…”
Section: Carbapenemase‐associated Mgesmentioning
confidence: 84%